Farmers’ Awareness of Agricultural Schemes under Saansad Adarsh Gram Yojana in Varanasi (UP) - Saurabh Tiwari,; K.S. Kadian,; H.R. Meena,; M.S. Nain,; Sweety Mukherjee,; Amandeep Ranjan, (Indian Journal of Extension Education, 2023)
The study was conducted to analyse the effect of Saansad Adarsh Gram Yojana (SAGY) on farmers’ awareness of different agricultural schemes during 2021. The center and state government-sponsored schemes under the SAGY were taken into consideration. As per the need of farmers, 25 schemes were included as the indicator for awareness in the study. The investigation was carried out in two blocks of the Varanasi district of Uttar Pradesh state. A significant difference was seen in awareness among the farmers of model and non-model villages. Among crop-based schemes, almost 70% of farmers of model villages were aware of the soil health card which was highest followed by Paramparagat Krishi Vikash Yojana (66%) and financial assistance for improved seeds(65%). Sixty percent of farmers of model villages were aware of the artificial insemination of animals scheme which was highest followed by the national livestock mission (18.67 %). In model villages, the majority of the farmers were in the category of high and medium levels of awareness. Only 14.67 % of farmers were in the category of low level of awareness but from the non-model villages, the majority of farmers were in the category of low level of awareness.